Auditory training during development mitigates a hearing loss-induced perceptual deficit - Kang, Ramanjot; Sarro, Emma; Sanes, Dan (Frontiers in Systems Neuroscience, 2014)
Sensory experience during early development can shape the central nervous system and this is thought to influence adult perceptual skills. In the auditory system, early induction of conductive hearing loss (CHL) leads to deficits in central auditory coding properties in adult animals, and this is accompanied by diminished perceptual thresholds. In contrast, a brief regimen of auditory training during development can enhance the perceptual skills of animals when tested in adulthood. Here, we asked whether a brief period of training during development could compensate for the perceptual deficits displayed by adult animals reared with CHL. Juvenile gerbils with CHL, and age-matched controls, were trained on a frequency modulation (FM) detection task for 4 or 10 days. The performance of each group was subsequently assessed in adulthood, and compared to adults with normal hearing or adults raised with CHL that did not receive juvenile training. We show that as juveniles, both CHL and NH animals display similar FM detection thresholds that are not immediately impacted by the perceptual training. However, as adults, detection thresholds and psychometric function slopes of these animals were significantly improved. Importantly, CHL adults with juvenile training displayed thresholds that approached normal hearing adults. Additionally, we found that hearing impaired animals trained for 10 days displayed adult thresholds closer to untrained adults than those trained for 4 days. Thus, a relatively brief period of auditory training may compensate for the deleterious impact of hearing deprivation on auditory perception on the trained task.